PERANAN KOPERASI MAHASISWA DALAM MENGEMBANGKAN KARAKTER KEMANDIRIAN WARGA NEGARA: Studi Deskriptif Analitis pada Koperasi Mahasiswa Universitas Pendidikan Indonesia - Rahmi, Rizki Silvina (2013)
This research is motivated by the demands of global competition in the era that requires students to have the character of self-reliance and applied through student activities and KOPMA is one place for students to develop the independence of character. Formulation of the problem in this research is how the process of developing citizens of character independence through Cooperative Education Student at the University of Indonesia, the values change in what is perceived by members of the Indonesian Education University student cooperative after attending Kopma activities as stock in realizing independence in society, behavioral independence What are the most dominant was developed through a cooperative education student at the University of Indonesia, what are the constraints faced by Indonesian Education University Students' Cooperative in the process of developing the character of citizen independence and efforts. The basis of this research is the opinion expressed by Lickona (1991) which states that a good character has three interrelated parts: moral knowledge, moral feeling, and moral behavior. The approach taken in this study is qualitative, whereas the method used is descriptive analytic to get the real picture, actual, and contextual about the above phenomenon. Research conducted at the University of Cooperative Education Student of Indonesia, while the subject of research KOPMA Supervisor, KOPMA Chairman, Chairman of NRM and Business Sectors KOPMA and members. The results obtained by researchers, namely: 1) The process of character development in student independence KOPMA Indonesia University of Education performed through a series of regeneration as well as the distribution of interests and talents possessed by members KOPMA. 2) After going through a variety of educational process, students experience a change in terms of independence emotions (emotional autonomy), independent of behavior (behavior autonomy) and the independence of the value (value autonomy). 3) the independence of the most dominant behavior developed through Cooperative Education Student at the University of Indonesia, including responsibilities, creative and innovative, and never give up attitude. 4) The constraints faced by the University Students' Cooperative Education Indonesian independence in the process of developing a character as a citizen member of the lack of interest of students to follow KOPMA, difficult to set the appropriate time to conduct activities KOPMA, difficulty in coordination with supervisor KOPMA, because its busy . 5) The efforts of the University Students' Cooperative Education Indonesia to overcome the obstacles that occur in the process of developing a character independence as a member of the citizens of creating ideas that are more creative to make students more interested in following the activities KOPMA, better time management by the board KOPMA when implement activities, coordination with supervisor KOPMA done by phone, sms, e-mail or other social media, so it is not hampered by the busyness supervisor.